Navigated versus Non-Navigated Intraoperative Ultrasound: Is There Any Impact on the Extent of Resection of High-Grade Gliomas? A Retrospective Clinical Analysis - Renovanz, Mirjam; Hickmann, Anne-Katrin; Henkel, Christine; Nadji-Ohl, Minou; Hopf, Nikolai J. (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2014)
Introduction The extent of tumor resection is a significant predictor of survival in high-grade gliomas. In recent years, several authors showed the benefit of intraoperative ultrasound partially matched with magnetic resonance imaging (MRI). The aim of this study was to find out if intraoperative neuronavigation in combination with intraoperative ultrasound has any impact on the complete resection of gliomas. A comparison between the ultrasound-controlled resection of brain tumors and operations controlled by navigated ultrasound was performed.Materials and Methods A total of 92 patients (54 men and 39 women) with a mean age of 53.2 years underwent 93 operations over a period of 4 years (2007–2010). They harbored a tumor with suspicion of glioma; 32 of them had undergone previous surgery, and additional chemotherapy, and 29 of them had undergone irradiation. Overall, 49 operations were performed with navigated ultrasound (group A) and 44 with non-navigated ultrasound (group B). A standardized early postoperative MRI was performed . Complete or gross total resection (GTR) was defined by a resection of ≥ 95% of the tumor. Skin incision and craniotomy were planned after registration of the neuronavigation system. The ultrasound system was used systematically before and after opening the dura, and during and at the end of resection.Results GTR could be achieved in 28 of 49 cases in group A and in 23 of 44 cases in group B. In group A, sensitivity and specificity of tumor remnants detected by ultrasound were higher than in group B. Concerning recurrent gliomas, the sensitivity of ultrasound visualizing tumor remnants was lower than in primary tumors. In case of preoperatively planned GTR, in both groups (navigated and non-navigated ultrasound) similar tumor remnant sizes were postoperatively detected by MRI. In nine cases the removal was incomplete because of eloquently located tumors. There was no significant difference between navigated and not-navigated ultrasound concerning GTR (p > 0.05).Conclusion Navigated ultrasound is an important technical tool that helps in intraoperative orientation. Further prospective investigation is needed to assess the impact on GTR.
Keywords: glioma; ultrasound; extent of resection; navigation